Entorno familiar y la salud mental en los niños de la Unidad Educativa Manuel Villamarin Ortiz, año 2019 - Ramirez Reyes, Jorge Elias (2019)
This research aims to establish how the family environment affects the mental health of the students of the Manuel Villamarin Ortiz Educational Unit and, in turn, to know their changes in academic performance. The population was chosen in this institution since in their classrooms there have been behavioral problems during the last years by students both at home and inside the institution, these manifest actions of misconduct in their behavior such as: bullying , lack of communication, low academic performance, among other behaviors of great interest. The results of the research are supported by analyzing the results of the surveys taken by students, family members and teachers, which concluded that the majority of children with academic behavior problems are the result of a family environment since they are often very conflictive causing students to show a certain degree of lack of concentration in their academic process. The proposal established in this research is aimed at finding solutions to the problem raised by strengthening family ties, developing social skills, improving the emotional life of students, improving the academic family environment, through strategies, workshops and speakers with bases psychological